2004
DOI: 10.3390/ijerph2004020100
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic and Cytotoxic Effects of Pentachlorophenol to AML 12 Mouse Hepatocytes

Abstract: Pentachlorophenol (PCP), an organochlorine fungicide, is extensively used in the United States for the protection of wood products. Moreover, widespread agricultural, domestic, and industrial applications have caused PCP-contaminants to enter the food chain from the environment. There is accumulating evidence indicating that PCP is highly toxic to humans, and causes injury to major organs including the lung, liver, kidneys, heart, and brain. While PCP has been shown to induce systemic toxicity and carcinogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Expression and relative abundance of the 35–kDa cyclin D1 in AML 12 mouse hepatocytes exposed to PCP and NRG1-β + PCP treatments for 48 h are shown in Figure 7 . We have previously reported that PCP has the ability to elicit a mitogenic response in HepG 2 cells, primary catfish hepatocytes, and AML 12 mouse hepatocytes [ 19 , 20 , 23 ]. In this experiment, we observed a dose-dependent overexpression of cyclin D1 with relative abundances of 66,371 at 8 μg NRG1-β+PCP/mL, 42,764 at 8 µg PCP/mL, and 48,757 at 16 µg NRG1-β+PCP/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression and relative abundance of the 35–kDa cyclin D1 in AML 12 mouse hepatocytes exposed to PCP and NRG1-β + PCP treatments for 48 h are shown in Figure 7 . We have previously reported that PCP has the ability to elicit a mitogenic response in HepG 2 cells, primary catfish hepatocytes, and AML 12 mouse hepatocytes [ 19 , 20 , 23 ]. In this experiment, we observed a dose-dependent overexpression of cyclin D1 with relative abundances of 66,371 at 8 μg NRG1-β+PCP/mL, 42,764 at 8 µg PCP/mL, and 48,757 at 16 µg NRG1-β+PCP/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings from our laboratory have demonstrated that PCP has the ability to undergo Phase I biotransformation in the liver (CYP1A1 and XRE), to cause cell proliferation ( c-fos ), to cause growth arrest and DNA damage (GADD153 and p53), to influence the toxicokinetics of metal ions (HMTIIA), and to induce proteotoxic effects (HSP70 and GRP78) in HepG 2 cells [ 18 ]. We have also reported that PCP exerts both cytotoxic and mitogenic effects in human liver carcinoma (HepG 2 ) cells, primary catfish hepatocytes, and AML 12 mouse hepatocytes [ 19 , 20 ]. In the present study, we hypothesized that NRG1-β will exert a cytoprotective effect in PCP-treated AML 12 mouse hepatocytes in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…After 24 h of incubation at 37 C in a CO 2 incubator, cells were overlaid with DMEM medium containing test compounds (3.12e100 mg/ml for 5810599 & 6012954 and upto 10Â MIC for 6624116 & 5655606) along with DMSO control in triplicate wells. After incubation at 37 C for 24 h, cellular viability was measured by using 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay [29]. Formation of formazan salt by mitochondrial dehydrogenases was measured at 570 nm.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Furthermore, MMP across the inner membrane has been linked to a variety of mitochondrial functions including: ATP synthesis, Ca 2+ homeostasis, metabolite transport and the import of mitochondrial proteins [62], thereby being an indicator of the health of the organelle in cells exposed to a variety of toxic compounds. PCP is a wellknown uncoupler of oxidative phosphorylation and its main mechanism of toxicity has been attributed to the resulting increase in aerobic metabolism and increasing heat production (hyperpyrexia) [63]. PCP has also been classified as a protonophoric uncoupler, which depletes the proton gradient by translocating protons from the intermembrane space into the mitochondrial matrix [64].…”
Section: Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…The present study observed that PCP caused mitochondrial depolarization. This is supported by the fact that PCP is a well-known uncoupler of oxidative phosphorylation that depletes the proton gradient, by translocating protons from the intermembrane space into the mitochondrial matrix [63], and induces aerobic metabolism and heat production [59].…”
Section: On the Mechanism(s) Of Toxicity Of The Test Compoundsmentioning
confidence: 99%